New NASICON-type Li2Ni2(MoO4)3 as a positive electrode material for rechargeable lithium batteries - PRABAHARAN, S (2004)
A new lithiated NASICON-type polyanion material, Li2Ni2(MoO4)(3) was synthesized for the first time by means of a low temperature approach involving glycine as a mild combustion agent. The synthesized product, Li2Ni2(MoO4)(3), was found to crystallize in an ortborhombic structure (space group Pmcn) with cell parameters a = 10.424(4) Angstrom, b = 17.525(1) Angstrom and c = 5.074(3) Angstrom. The electronic state of each element present in the new material was confirmed by X-ray photoelectron spectroscopic (XPS) analysis. The metals content present in the new material was analyzed using inductively coupled plasma emission spectroscopy (ICP-AES). Fiber-like submicrometre grains were evident from scanning electron microscopy (SEM) analysis of the annealed powders. The electrochemical performance of the new material was examined in a half-cell configuration against lithium metal employing a conventional Li+ non-aqueous electrolyte. Slow scan cyclic voltammetry (SSCV) revealed the electrochemical reversibility of the material between the potential window of 4.9 V (charge cutoff) and 1.5 V (discharge cutoff). Reversible extraction/insertion of Li+ from and into the framework structure delivered a reversible capacity of similar to115 mA h/g (4.9-1.5-V window) after the first charge/discharge cycle. (C) 2004 Elsevier B.V. All rights reserved.